The voice of radio in the battle for equal rights: Evidence from the U.S. South. (8th March 2022) - Bernini, Andrea
Abstract: Although the 1960s race riots have gone down in history as America's most violent and destructive ethnic civil disturbances, a consensus on the factors able to explain their insurgence is yet to be found. Using a novel data set on the universe of radio stations airing Black‐appeal programming, the effect of the media on riots is found to be sizable and statistically significant. A marginal (1%) increase in signal reception from these stations is estimated to lead to a 2.4% and 4.1% rise in the mean levels of the frequency and intensity of riots, respectively. Several mechanisms behind this result are considered, with the quantity, quality, and length of exposure to radio programming all being decisive factors.